Photomorphogenesis in the Picocyanobacterium Cyanobium gracile Includes Increased Phycobilisome Abundance Under Blue Light, Phycobilisome Decoupling Under Near Far-Red Light, and Wavelength-Specific Photoprotective Strategies - Bernát, Gábor; Zavřel, Tomáš; Kotabová, Eva; Kovács, László; Steinbach, Gábor; Vörös, Lajos; Prášil, Ondřej; Somogyi, Boglárka; Tóth, Viktor R. (Frontiers in Plant Science, 2021)
Photomorphogenesis is a process by which photosynthetic organisms perceive external light parameters, including light quality (color), and adjust cellular metabolism, growth rates and other parameters, in order to survive in a changing light environment. In this study we comprehensively explored the light color acclimation of Cyanobium gracile, a common cyanobacterium in turbid freshwater shallow lakes, using nine different monochromatic growth lights covering the whole visible spectrum from 435 nm to 687 nm. According to incident light wavelength, C. gracile cells performed great plasticity in terms of pigment composition, antenna size, and photosystem stoichiometry, to optimize their photosynthetic performance and to redox poise their intersystem electron transport chain. In spite of such compensatory strategies, C. gracile, like other cyanobacteria, uses blue and near far-red light less efficiently than orange or red light, which involves moderate growth rates, reduced cell volumes and lower electron transport rates. Unfavorable light conditions, where neither chlorophyll nor phycobilisomes absorb light sufficiently, are compensated by an enhanced antenna size. Increasing the wavelength of the growth light is accompanied by increasing photosystem II to photosystem I ratios, which involve better light utilization in the red spectral region. This is surprisingly accompanied by a partial excitonic antenna decoupling, which was the highest in the cells grown under 687 nm light. So far, a similar phenomenon is known to be induced only by strong light; here we demonstrate that under certain physiological conditions such decoupling is also possible to be induced by weak light. This suggests that suboptimal photosynthetic performance of the near far-red light grown C. gracile cells is due to a solid redox- and/or signal-imbalance, which leads to the activation of this short-term light acclimation process. Using a variety of photo-biophysical methods, we also demonstrate that under blue wavelengths, excessive light is quenched through orange carotenoid protein mediated non-photochemical quenching, whereas under orange / red wavelengths state transitions are involved in photoprotection.